The theta-syllable: a unit of speech information defined by cortical function - Ghitza, Oded (Frontiers in Psychology, 2013)
A recent commentary (Oscillators and syllables: a cautionary note. Cummins, 2012) questions the validity of a class of speech perception models inspired by the possible role of neuronal oscillations in decoding speech (e.g., Ghitza 2011, Giraud & Poeppel 2012). In arguing against the approach, Cummins raises a cautionary flag “from a phonetician’s point of view.” Here we respond to his arguments from an auditory processing viewpoint, referring to a phenomenological model of Ghitza (2011) taken as a representative of the criticized approach. We shall conclude by proposing the theta-syllable as an information unit defined by cortical function – an alternative to the conventional, ambiguously defined syllable. In the large context, the resulting discussion debate should be viewed as a subtext of acoustic and auditory phonetics vs. articulatory and motor theories of speech reception.